Education of musical culture of pupils in a context of humanistic pedagogics (Pedagogy of Higher and Secondary Education, 2007)
Modern approaches to the aims of musical education that are conceptually important in terms of humanistically oriented pedagogics are regarded in the article.
Keywords: musical education; humanistic pedagogics